6th International Symposium on Telecommunications (IST) 2012
DOI: 10.1109/istel.2012.6483135
|View full text |Cite
|
Sign up to set email alerts
|

A lower capacity bound of secure end to end data transmission via GSM network

Abstract: Global System for Mobile communications (GSM) is a widely spread, reliable and P2P channel through all over the world. These characteristics make GSM a channel suitable for a variety of applications in different domains especially security applications such as secure voice communication. Performance and usage of GSM applications extremely depends on the transmission data rate. Hence, transmitting data over GSM is still an attractive topic for research. This paper considers the problem of digital data transmiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…GSM was first introduced in Europe in 1991 and today is one of the most popular digital mobile telecommunications systems widely used over the world [3]. Due to the increase of the number and the requirement of GSM subscriber the GSM is still an attractive area for research in the field of mobile telecommunication [3][4][5].…”
Section: Gsmmentioning
confidence: 99%
“…GSM was first introduced in Europe in 1991 and today is one of the most popular digital mobile telecommunications systems widely used over the world [3]. Due to the increase of the number and the requirement of GSM subscriber the GSM is still an attractive area for research in the field of mobile telecommunication [3][4][5].…”
Section: Gsmmentioning
confidence: 99%
“…As classified by [3, 4], prior researches on data transmission over voice channels have proposed three different approaches of ‘parameter mapping’ [15], ‘codebook optimisation’ [16–18] and ‘modulation optimisation’ [19, 20] to overcome voice channel non‐idealities [3, 4, 21]. These approaches are well compared in [4].…”
Section: Introductionmentioning
confidence: 99%
“…Shahbazi et al [21] used exhaustive search algorithm over observed human speech waveforms to find optimum symbols. Boloursaz et al [22][23][24] and Kazemi et al [25] proposed a heuristic algorithm optimising the codebook for a maximised capacity. The highest achieved data rate of this group is 4 kbps with the symbol error rate (SER) of 2.5%.…”
Section: Introductionmentioning
confidence: 99%